The Ordinary Market For Fake Likes - Beauvisage, Thomas; Mellet, Kevin (AoIR Selected Papers of Internet Research, 2017)
This paper aims to describe the rise and stabilization of the market for fake likes and followers, and to understand how it became an important piece in the online reputation industry puzzle. We rely on an empirical material allowing us to document the emergence and stabilization of this market, its crafting techniques, and its place within the reputation economy since 2013. We show that the industry of fake likes has benefited in its early years from the development of the social media marketing industry and its focalization on meters. Some years later, counterfeiting meters on social media has become a more standardized and autonomous business, based on a small set of crafting methods, delivering a small range of services, and attracting a specific demand for social signals (singers, small businesses, etc.). Finally, we claim that the fake likes industry is part of a wider range of online manipulations and automations that slip into the interstices left vacant by the absence of legal standards and by the more or less strict application of the Terms of service of major web players and social media websites.